Downregulation of Ca2+-Activated Cl− Channel TMEM16A Mediated by Angiotensin II in Cirrhotic Portal Hypertensive Mice - Kondo, Rubii; Furukawa, Nami; Deguchi, Akari; Kawata, Naoki; Suzuki, Yoshiaki; Imaizumi, Yuji; Yamamura, Hisao (Frontiers in Pharmacology, 2022)
Portal hypertension is defined as an increased pressure in the portal venous system and occurs as a major complication in chronic liver diseases. The pathological mechanism underlying the pathogenesis and development of portal hypertension has been extensively investigated. Vascular tone of portal vein smooth muscles (PVSMs) is regulated by the activities of several ion channels, including Ca2+-activated Cl- (ClCa) channels. TMEM16A is mainly responsible for ClCa channel conductance in vascular smooth muscle cells, including portal vein smooth muscle cells (PVSMCs). In the present study, the functional roles of TMEM16A channels were examined using two experimental portal hypertensive models, bile duct ligation (BDL) mice with cirrhotic portal hypertension and partial portal vein ligation (PPVL) mice with non-cirrhotic portal hypertension. Expression analyses revealed that the expression of TMEM16A was downregulated in BDL-PVSMs, but not in PPVL-PVSMs. Whole-cell ClCa currents were smaller in BDL-PVSMCs than in sham- and PPVL-PVSMCs. The amplitude of spontaneous contractions was smaller and the frequency was higher in BDL-PVSMs than in sham- and PPVL-PVSMs. Spontaneous contractions sensitive to a specific inhibitor of TMEM16A channels, T16Ainh-A01, were reduced in BDL-PVSMs. Furthermore, in normal PVSMs, the downregulation of TMEM16A expression was mimicked by the exposure to angiotensin II, but not to bilirubin. This study suggests that the activity of ClCa channels is attenuated by the downregulation of TMEM16A expression in PVSMCs associated with cirrhotic portal hypertension, which is partly mediated by increased angiotensin II in cirrhosis.